2013
DOI: 10.1126/science.1234689
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of Conformer-Dependent Reactivity of the Criegee Intermediate CH 3 CHOO

Abstract: Although carbonyl oxides, "Criegee intermediates," have long been implicated in tropospheric oxidation, there have been few direct measurements of their kinetics, and only for the simplest compound in the class, CH2OO. Here, we report production and reaction kinetics of the next larger Criegee intermediate, CH3CHOO. Moreover, we independently probed the two distinct CH3CHOO conformers, syn- and anti-, both of which react readily with SO2 and with NO2. We demonstrate that anti-CH3CHOO is substantially more reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

44
604
4
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 409 publications
(662 citation statements)
references
References 45 publications
(68 reference statements)
44
604
4
10
Order By: Relevance
“…Experimental results (Table 1) show that CH 2 OO and anti-CH 3 CHOO react with water vapor very quickly (3,(22)(23)(24). Thus, their steady-state concentrations would be too low to have a significant impact in SO 2 oxidation under typical atmospheric conditions, as shown in modeling results (15,16).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Experimental results (Table 1) show that CH 2 OO and anti-CH 3 CHOO react with water vapor very quickly (3,(22)(23)(24). Thus, their steady-state concentrations would be too low to have a significant impact in SO 2 oxidation under typical atmospheric conditions, as shown in modeling results (15,16).…”
mentioning
confidence: 96%
“…Although it has been shown that CIs may react very fast with SO 2 , NO 2 , and organic acids (2,3,14), the reactions of CIs with atmospheric water vapor would still strongly influence the fates and concentrations of atmospheric CIs (see Fig. 1 for a simplified schematic).…”
mentioning
confidence: 99%
See 3 more Smart Citations